2017
DOI: 10.3390/molecules22071050
|View full text |Cite
|
Sign up to set email alerts
|

Myrtaceae Plant Essential Oils and their β-Triketone Components as Insecticides against Drosophila suzukii

Abstract: Spotted wing drosophila (SWD, Drosophila suzukii (Matsumura), Diptera: Drosophilidae) is recognized as an economically important pest in North America and Europe as well as in Asia. Assessments were made for fumigant and contact toxicities of six Myrtaceae plant essential oils (EOs) and their components to find new alternative types of insecticides active against SWD. Among the EOs tested, Leptospermum citratum EO, consisting mainly of geranial and neral, exhibited effective fumigant activity. Median lethal do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…These findings highlight the need to explore the potential for development and commercialization of L. scoparium essential oil as a mosquito larvicide. Most of the chemical constituents identified in this study have been reported in L. scoparium essential oil albeit at different quantities [9,13,16,35,36]. These differences are expected because the chemical composition of essential oils is known to vary by plant geographic origin, stage of development, growing conditions, developmental stage of the plant, method of extraction, solvent used for extraction, and photosensitivity of some compounds in the extract [36][37][38].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These findings highlight the need to explore the potential for development and commercialization of L. scoparium essential oil as a mosquito larvicide. Most of the chemical constituents identified in this study have been reported in L. scoparium essential oil albeit at different quantities [9,13,16,35,36]. These differences are expected because the chemical composition of essential oils is known to vary by plant geographic origin, stage of development, growing conditions, developmental stage of the plant, method of extraction, solvent used for extraction, and photosensitivity of some compounds in the extract [36][37][38].…”
Section: Discussionmentioning
confidence: 83%
“…Leptospermum scoparium essential oil has been shown to be toxic against the spotted wing drosophila Drosophila suzukii Matsumura [16] and several species of mites [13][14][15][16], and also can synergize the activity of some essential oils against mosquito larvae [4]. Leptospermum scoparium essential oil has also been shown to be an attractive bait for the redbay ambrosia beetle, Xyleborus glabratus [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact toxicity of the non-polar fraction, made up of sesquiterpene hydrocarbons, was significantly lower than the toxicity of the polar fraction. The triketone fraction as part of the polar fraction was mainly composed of flavesone, isoleptospermone and leptospermone (Park et al 2017). For Leptospermum ericoides, the polar fraction was 67-fold more effective than the non-polar fraction for males and 134-fold more effective for females.…”
Section: Topical Applicationmentioning
confidence: 96%
“…Among the tested substances, the most effective were Leptospermum ericoides and Leptospermum scoparium EO, the polar fraction of those EO and L. scoparium EO triketone fraction with LD 50 values between 0.13 and 0.71 μg/fly for males and 0.22 and 1.23 μg/fly for females (Fig. 2, Jang et al 2017;Kim et al 2016aKim et al , 2016bPark et al 2017Park et al , 2016. The contact toxicity of the non-polar fraction, made up of sesquiterpene hydrocarbons, was significantly lower than the toxicity of the polar fraction.…”
Section: Topical Applicationmentioning
confidence: 97%